Análise dos impactos da EBSERH no desempenho dos hospitais universitários federais - Orlandi, Daniele de Paula (2016)
The present study investigated the impact of the adherence of the Federal University Hospitals to the Hospital Service Brazilian Company (EBSERH) in the care and teaching execution considering the three phases of the transition process. The pattern was composed of 32 federal university hospitals between 2011 and 2015. Among those, 24 adhered contractually to the EBSERH and 8 did not adhere. A model of the data envoltory analysis was used (DEA) to estimate the execution of the hospitals and, in the second phase, the obtained score was applied as dependent variable in Tobit regression model (truncate between 0 and 1) with hospital and teaching indicators as independent variables. The obtained results showed that the administration by the HSBC does not impact statistically the efficiency scores of the evaluated hospitals in none of the transition process phases. Nonetheless, the employees for bed and teaching intensity variables showed positive association with the execution of the hospitals and the average time of stay and dedication to the teaching variables had opposed behavior. New analysis of the impact of the adherence of the hospitals to the HSBC must be done after wide consolidation of the company as a way to evaluate the administration policy of such an important segment of the public services at long term